Kirovograd region deanthroponym place name’s peculiarities (based on the Kirovohrad region) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article analyzes the formation ways and lexical-semantic features of deanthroponym place names, some structural groups, variations in synchrony and diachrony are defined, statistics is submitted.
Keywords: deanthroponym place name; variations in synchrony and diachrony; derivation stem; suffixes